Education Programme Improvement Motor Skills Through Games Creativity for Prospective Teachers - Joan Rhobi Andrianto; Basuki; Rendra Wahyu Pradana; Tiara Dwi R (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Based on this community service activity related to the problem of understanding motor skills games programmes, in this case, material or activities are needed to support prospective teachers' understanding of games programmes. The method used in this case is related to education for prospective teachers associated with games programmes to improve children's motor skills. The participants of this activity were 82 students who were taking a small games course in the physical education study programme. The results of this activity were seen from the initial test results, which were in the poor category (54.88%), and the final test results, which were in the fair category (36.59%) and also good (19.51%). Thus, it can be concluded that the results of this activity had a positive impact on prospective teachers in terms of developing their knowledge about games for motor skills.